OPTIMIZATION OF WORK QUALITY IN LOW-COST APARTMENT CONSTRUCTION THROUGH OHS COMPLIANCE, LEADERSHIP AND THE MEDIATING ROLE OF WORK MOTIVATION - Dudi Mustofa; Mawardi Amin (RADJA PUBLIKA, 2025)
This study is a quantitative research using an explanatory approach that aims to analyze the influence of compliance with the Occupational Health and Safety (OHS) Program and leadership on the work quality of employees in the low-cost apartment construction project in DKI Jakarta, both directly and indirectly through work motivation as a mediating variable. The population of this study consists of 800 project implementation employees at one of regional owned enterprises engaged in the property and infrastructure sector, with a sample of 267 respondents determined using the Slovin formula at a 5% margin of error. Data were collected through a survey using a Likert-scale questionnaire and analyzed using the Structural Equation Modeling (SEM) method with the help of AMOS software version 22.00. The results show that compliance with the OHS Program has a significant positive effect on work quality but does not significantly affect work motivation. Leadership has a significant positive effect on both work motivation and work quality. Furthermore, work motivation serves as a significant mediating variable in bridging the effects of the OHS Program and leadership on work quality. The mediating effect of work motivation on the relationship between leadership and work quality is stronger than its effect on the relationship between the OHS Program and work quality. These findings indicate that in addition to the importance of implementing the OHS Program, effective leadership plays a strategic role in enhancing the motivation and work quality of construction project employees.